Occupational and Environmental Health Benefits of Smoking ban not yet Arrived in Austrian Youth - Berger, Julia; Neuberger, Manfred (International Journal of Occupational and Environmental Medicine, 2020)
The aim was to record the smoking behaviour of 13- to 16-year-old Austrian pupils and to investigate changes in smoking behaviour following amendments of legislation and gender-specific differences. The survey took place in Vienna, Lower Austria, Burgenland, Styria and Carinthia and was conducted at eight different school types. The data was collected by means of a questionnaire in a group setting at the beginning of a school lesson. The completion of the questionnaire was anonymous. 95,1% of the returned questionnaires could be used for this study, yielding data from a total of 1029 young people for analysis. 38.4% of the participants stated that they had at least once consumed tobacco or related products, with girls having tried them more often (41,6%) than boys (34,9%) (p = .028). At the time of the study, 3,3% used tobacco daily and 4,6% several times a week; thus 7,9% smoke regularly. Although friends or family are the most popular type of acquisition for girls and boys, girls buy their tobacco products from vending machines (11,6%) much more frequently than boys (6,0%) (p = .014) and prefer normal cigarettes (p < .001). The results of this study show that while the number of adolescents who smoke daily is decreasing, the number of occasional smokers is increasing. Already 38,4% of the 13 to 16-year olds have had some experience consuming tobacco. Austria must take the measures recommended by the WHO to reduce the smoking prevalence and protect minors from the health damage caused by tobacco smoke.
Keywords: Smoking Behaviour; Smoking Ban; Tobacco; Vending Machines; Gender-Specific Differences